2022
DOI: 10.11113/jurnalteknologi.v84.17542
|View full text |Cite
|
Sign up to set email alerts
|

Review: Ischemic Heart Disease and the Potential Role of Fenugreek (Trigonella Foenum Graecum Linn.) in Cardioprotection

Abstract: Ischemic heart disease, often known as coronary heart disease (CHD), is a term for heart disorders caused by narrowing heart arteries (coronary arteries) that provide blood to the heart's muscles. The body is prone to heart attacks when there is less oxygen supply (hypoxia) to the heart resulting a major cell death in the heart tissues. Cardiovascular disease (CVD) is the leading cause of death worldwide. Over the last few decades, the potential therapeutic effects of herbs and other types of complementary med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 113 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…They may help reduce inflammation in various parts of the body, potentially benefiting conditions like arthritis and respiratory issues (Kaveh et al., 2022 ). Because the combined effects of blood sugar regulation, cholesterol management, and antioxidant activity contribute to fenugreek seeds’ potential to support heart health, they may, therefore, help reduce the risk of cardiovascular diseases (Hanafi et al., 2022 ). Fenugreek seeds may have a positive impact on hormonal balance, and studies have shown their potential to alleviate symptoms of menopause and polycystic ovary syndrome (PCOS) (Nannar et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…They may help reduce inflammation in various parts of the body, potentially benefiting conditions like arthritis and respiratory issues (Kaveh et al., 2022 ). Because the combined effects of blood sugar regulation, cholesterol management, and antioxidant activity contribute to fenugreek seeds’ potential to support heart health, they may, therefore, help reduce the risk of cardiovascular diseases (Hanafi et al., 2022 ). Fenugreek seeds may have a positive impact on hormonal balance, and studies have shown their potential to alleviate symptoms of menopause and polycystic ovary syndrome (PCOS) (Nannar et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%